Análise de relevância de elementos de custo em manutenção e suporte de sistemas ERP nas IFES: uma abordagem baseada em TCO e ITIL - Corrêa, Sérgio Luís Lima (2015)
Integrated Systems Management, known as ERP (Enterprise Resource Planning), are developed and maintained by IFES (Federal Institutions of Higher Education) for the performance of activities that concern them, in addition, its scope allows obtaining management information becoming valuable strategic resource. Recent guidelines of the supervisory bodies and government control, aimed at increasing efficiency, higher productivity of public administration, and cost reduction have led IFES to adopt IT governance policies. ERP systems are usually very comprehensive and expensive, so their costs should be measured, not only acquisition costs, but mainly maintenance and support costs. In this regard, in order to determine the cost elements to measure the costs of maintenance and support in managing ERP systems, there was motivation for this research on the TCO methodology (Total Cost of Ownership) supported by ITIL framework processes (Information Technology Infrastructure Library). This work, descriptive, identified and listed from the literature, the most obvious cost elements in TCO and ITIL. Then a web questionnaire was administered, along with experts in ERP systems management of IFES, aiming to map their perception of relevance of these cost factors listed in the survey. The results show the cost elements ordered by relevance and frequency that the maintenance and ERP systems support and the expected contribution is to facilitate the measurement of these costs